2023
DOI: 10.3390/ijms24065673
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Gut Microbiome Differences between High and Low Aortic Arch Calcification Score in Patients with Chronic Diseases

Abstract: Gut dysbiosis can induce chronic inflammation and contribute to atherosclerosis and vascular calcification. The aortic arch calcification (AoAC) score is a simple, noninvasive, and semiquantitative assessment tool to evaluate vascular calcification on chest radiographs. Few studies have discussed the relationship between gut microbiota and AoAC. Therefore, this study aimed to compare the microbiota composition between patients with chronic diseases and high or low AoAC scores. A total of 186 patients (118 male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 92 publications
0
6
0
Order By: Relevance
“…in α-diversity along with a heightened prevalence of Clostridia species; those with lower AoAC scores exhibited a more favorable microbial profile, characterized by a higher abundance of beneficial bacteria such as Agathobacter (31). In another study involving 73 hemodialysis patients, notable distinctions in gut flora were discerned across various VC groups (32).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…in α-diversity along with a heightened prevalence of Clostridia species; those with lower AoAC scores exhibited a more favorable microbial profile, characterized by a higher abundance of beneficial bacteria such as Agathobacter (31). In another study involving 73 hemodialysis patients, notable distinctions in gut flora were discerned across various VC groups (32).…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have observed changes in the gut flora of VC patients. An observational study investigated differences in gut flora composition among chronic disease patients with varying degrees of aortic arch calcification (AoAC) (31). Individuals with the highest AoAC scores displayed a significant decrease The results of subgroup analysis were adjusted for all covariates except the effect modifier.…”
Section: Discussionmentioning
confidence: 99%
“…[Eubacterium]_hallii_grou, Collinsella, Colidextribacter, NK4A214_group, Negativibacillus, Faecalitalea, Family_XIII_AD3011_group, Peptoniphilus, Fructilactobacillus, and Solobacterium were enriched in CAD patients. Among them, eight of these identi ed microbes, including Blautia, Fusicatenibacter, Monoglobus, Eubacterium, UCG-002, UCG-005, Collinsella, and NK4A214_group, have been reported to be associated with CAD, acute myocardial infarction, or CAD complicated with non-alcoholic fatty liver disease in previous studies [29,[37][38][39][40][41][42][43][44]. Notably, 10 microbes, including Sutterella, Lachnospiraceae_NK4A136_group, [Eubacterium]_hallii_grou, Colidextribacter, Negativibacillus, Faecalitalea, Family_XIII_AD3011_group, Peptoniphilus, Fructilactobacillus, and Solobacterium, were newly identi ed in the current investigation.…”
Section: Difference In Gut Microbiota Between Cad and Control Groupmentioning
confidence: 99%
“…Conversely, the high AoAC group exhibited an increased relative abundance of the class Bacilli. 14 Additionally, another study identified the enrichment of Acinetobacter in the blood as a potential risk factor for vascular calcification in chronic kidney disease. 15 Therefore, it is hypothesized that gut microbiota may influence the progression of T2DM and vascular calcification, particularly through dietary interventions involving different carbohydrate compositions.…”
Section: Introductionmentioning
confidence: 99%